Recent Advances in Application of Ionic Liquids in Electrolyte of Lithium Ion Batteries. (August 2021) - Niu, Huizhe; Wang, Le; Guan, Ping; Zhang, Nan; Yan, Chaoren; Ding, Minling; Guo, Xulong; Huang, Tongtong; Hu, Xiaoling
Highlights: Ionic liquids could solve the problem resulting from organic solvent-based liquid electrolytes in lithium ion batteries. Different types of ionic liquids-based hybrid electrolytes and gel polymer electrolytes. Applications and the main limitations of ionic liquids-based gel polymer electrolytes. Polymerized ionic liquids-ionic liquids-based electrolytes own promising perspective of potential application in lithium ion batteries. Abstract: Lithium ion Batteries (LiBs), as one of the most widely and primarily battery, have been playing an irreplaceable role in human life. They are not only essential for portable electronics, but also playing the dominant and prospective roles in the global effort to tackle the challenges of the renewable energy supply and air pollution at the same time. However, most LiBs assemble with organic solvent-based liquid electrolytes possessing the drawback of volatile, flammable and low decomposition temperature, so it suffers from toxicity, flammability, potential leakage, even explosion accidents when the LiBs are exposed to harsh conditions such as internal short circuits, high temperature and cell crush. To address those safety issues of organic liquid electrolytes, various ionic liquids (ILs) are used in the preparations of electrolytes for LiBs. In this article, a few application of ILs are reviewed by focusing on their use as electrolyte materials for LiBs. Due to their characteristic properties such as nonvolatility, inflammability, high thermal stability, and high ionic conductivity, ILs appear to meet the rigorous demands of the applications involved in liquid electrolytes, polymer composed electrolytes, and polymerized ionic liquids (PILs) composed electrolytes. Herein, the preparation, characteristic, the latest developments, and the perspective of potential application of those electrolytes comprised one or all of ILs and PILs in electrochemical storage devices which clearly focus on LiBs are summarized and discussed. Finally, the main challenges and perspective of ILs-based or ILs-PILs-based electrolytes are illustrated at the end of this review.